Financial network systemic risk contributions - Nikolaus Hautsch; Julia Schaumburg; Melanie Schienle (Goethe University Frankfurt, Center for Financial Studies (CFS), 2013)
We propose the realized systemic risk beta as a measure for financial companies' contribution to systemic risk given network interdependence between firms' tail risk exposures. Conditional on statistically pre-identified network spillover effects and market as well as balance sheet information, we define the realized systemic risk beta as the total time-varying marginal effect of a firm's Value-at-risk (VaR) on the system's VaR. Statistical inference reveals a multitude of relevant risk spillover channels and determines companies' systemic importance in the U.S. financial system. Our approach can be used to monitor companies' systemic importance allowing for a transparent macroprudential supervision.
urn:nbn:de:hebis:30:3-324971
Keywords: G01; G18; G32; G38; C21; C51; C63; 330; time-varying systemic risk contribution; systemic risk network; network topology estimation; Value at Risk